Influence of genetic type and level of concentrate in the finishing diet on carcass and meat quality traits in beef heifers - Lage, J. F. [UNESP]; Paulino, P. V. R.; Valadares Filho, S. C.; Souza, E. J. O.; Duarte, M. S.; Benedeti, P. D. B.; Souza, N. K. P.; Cox, R. B. (Elsevier B.V., 2012)
Carcass and meat quality traits of thirty-six feedlot beef heifers from different genetic groups (GG) fed at two concentrate levels (CL) were evaluated using 12- Nellore (NE), 12 - 1/2Angus x 1/2Nellore (AN) and 12 - 1/2Simmental x 1/2Nellore (SN) animals. Six heifers of each GG were randomly assigned into one of two treatments: concentrate at 0.8% or 1.2% of body weight (BW). Heifers fed concentrate at 0.8% of BW had greater (P<0.05) dressing percentage. None of the proximate analysis components of the beef were affected (P>0.05) by either CL or GG. Heifers from the AN group had higher (P<0.05) carcass weights, 12th rib fat thickness and lower dressing percentage (P<0.05) compared to the other groups. NE heifers had greater WBSF values (P<0.05) than the other genetic groups. Data suggest that the concentrate level can be reduced without compromising meat quality traits. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Angus; Feedlot; Nellore; Simmental